The Effect of Acute Breath-Holding Exercise in Different Conditions on Cognitive Performance in Free Divers - Gökhan Tuna; Egemen Manci; Erkan Günay, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
There is a growing trend towards studying human cognition in aquatic environments. At present, there exists a dearth of scholarly investigations pertaining to the immediate effects on executive functions subsequent to a solitary breath-holding training session within the cohort of professional free divers who engage in highly strenuous activities that test their physiological boundaries. The objective of this study was to investigate the immediate impact of breath-holding exercises conducted in varying environments (water and land) on the executive functions of professional diving athletes. The research comprised a sample of 18 male individuals engaged in competitive free diving. The experimental design encompassed four distinct sessions: i) an initial phase dedicated to familiarising participants with the N-back test; ii) a subsequent phase involving the collection of baseline and control measurements for the N-back test; iii) a session focused on obtaining anthropometric measurements; and iv) a final session dedicated to measuring lung capacity. The cognitive assessments were conducted subsequent to the breath-holding exercise protocol, which occurred subsequent to both the land and water sessions. The results indicated a significant difference in reaction times between breath-holding exercises conducted on land and in water (p =.021). The computation of delta values was employed to ascertain alterations in cognitive test outcomes under distinct conditions (water and land) in comparison to the control condition. The findings revealed a statistically significant decline in cognitive performance in the water condition relative to the land condition (z:-2.025, p= 0.043, r= -0.544). This study claims that the implementation of breath-holding exercise training in surface water conditions among divers could potentially result in adverse effects on executive functions. Moreover, it has been observed that the identical breath-holding exercises, when executed in terrestrial environments, exhibit a moderate enhancement of executive functions. The present study posits that the aforementioned findings will make a valuable contribution to the development of training methodologies for athletes and coaches involved in the discipline of freediving. Additionally, these findings are anticipated to offer valuable insights into the physiological well-being of divers.